Self-consistent modelling of heating synergy between NBI and ICRH in JET deuterium plasmas. (5th June 2019) - Joly, J; Garcia, J; Imbeaux, F; Dumont, R; Schneider, M; Johnson, T; Artaud, J F
Abstract: Auxiliary heating is essential to initiate fusion in future tokamaks. In particular, ion heating tends to maximise the alpha power generation by increasing the thermal ion temperature. In order to simulate the plasma heating by ion cyclotron radio frequency waves, the EVE code, a full wave code for IC wave propagation, and SPOT, an orbit following Monte Carlo code combined with the RFOF library which calculates the absorption of wave by ions, have been coupled together. This new package is used for simulating JET plasmas with strong interplay between ion cyclotron resonant heating and neutral beam injection. Simulations shows that up to 20% of the neutron rate generated in recent JET D plasmas is due to the synergy between both heating mechanisms. However, the H concentration plays a critical role on such interplay, because the synergy efficiency weakens with the H concentration. Therefore, the control of the H concentration is mandatory for optimising the fusion reaction rate generation at JET.